Prostate cancer: estimating the benefits of PSA screening. - Vickers, A; Lilja, H (2009)
Two groundbreaking trials have this year reported conflicting results as to the benefit of screening for prostate cancer. Careful interpretation in the light of contemporary data is needed to reveal the value of this intervention.